Analisa Penerapan Metode MABAC dengan Pembobotan Entropy dalam Penilaian Kinerja Dosen di Era Society 5.0 - Ahyuna, Ahyuna; Rahman, Ben; Nugroho, Fifto; Nirawana, I Wayan Sugianta; Karim, Abdul (Forum Kerjasama Pendidikan Tinggi, 2023)
In the era of society 5.0, it is very influential on the education sector which is experiencing increasingly sophisticated technological changes, so that lecturers are expected to be able to combine learning with technology so that students' insight into technology is growing. However, in the case of a performance appraisal process, several problems often occur because the large number of lecturers will affect the time of the performance appraisal process. In assessing the performance of lecturers in the era of society 5.0, there are several criteria including Dynamic, Innovative, Number of Scientific Publishes, Discipline and Digital Skills. Therefore, the author applies a MABAC and ENTROPY method in order to find accurate and logical results. So with that, the author adopted a method and produced the highest ranking, namely on behalf of Dito Putro Utomo with a total value of 0.39925